(untitled) (Experimental biology, 2024)
The study focuses on analyzing the spread of viral infections in potato crops in the Almaty region of Kazakhstan. The work emphasizes the significance of the issue of viral diseases in potatoes, considering their impact on crop yield and the quality of agricultural products. During the study, the most prevalent viruses, including PVY, PVS, PVM, and PLRV, were identified, and their impact on potato crops was examined. The authors employed molecular methods for the diagnosis of infections, enabling precise identification of viral agents and assessment of their extent of spread. The obtained results emphasize the necessity of developing and implementing comprehensive strategies to combat viral diseases of potatoes, including the use of resistant varieties and control of virus vectors.